Application of Incremental Dynamic Analysis (IDA) Method for Studying the Dynamic Behavior of Structures During Earthquakes - Javanpour, M.; Zarfam, P. (Engineering, Technology & Applied Science Research, 2017)
Prediction of existing buildings’ vulnerability by future earthquakes is one of the most essential topics in structural engineering. Modeling steel structures is a giant step in determining the damage caused by the earthquake, as such structures are increasingly being used in constructions. Hence, two same-order steel structures with two types of structural systems were selected (coaxial moment frames and moment frame). In most cases, a specific structure needs to satisfy several functional levels. For this purpose, a method is required to determine the input request to the structures under possible earthquakes. Therefore, the Incremental Dynamic Analysis (IDA) was preferred to the Push-Over non-linear static method for the analysis and design of the considered steel structures, due its accuracy and effect of higher modes at the same time intervals. OpenSees software was used to perform accurate nonlinear analysis of the steel structure. Two parameters (spectral acceleration and maximum ground acceleration) were introduced to the modeled frames to compare the numerical correlations of seismic vulnerability obtained by two statistical methods based on the "log-normal distribution" and "logistics distribution", and finally, the parameters of displacement and drift were assessed after analysis.